P366 A service evaluation of pre-operative nutritional optimisation in patients with Crohn's disease using exclusive enteral nutrition with or without supplementary parenteral nutrition. (25th January 2019) - O'Hanlon, D; Sandall, A; Darakhshan, A; Williams, A; Westcott, E; Patel, K; Irving, P; Lomer, M
Abstract: Background: Malnutrition is a significant problem in patients with Crohn's disease (CD) who need surgery and leads to poor post-operative outcomes. The ideal method of pre-operative nutritional optimisation in CD is not known. Limited evidence suggests that exclusive enteral nutrition (EEN) improves nutritional and surgical outcomes. Some patients require supplementary parenteral nutrition (PN) to meet their nutrition requirements due to increased disease severity and/or phenotype. This service evaluation assessed nutritional and surgical outcomes in patients with CD who received pre-operative nutritional optimisation with EEN or supplementary PN. Methods: Patients with stricturing and/or penetrating CD, who underwent surgery from January 2016 to December 2017 were offered exclusive enteral nutrition (EEN) for at least 6 weeks pre-operatively. Patients who could not meet nutrition requirements from EEN were offered supplementary PN. Comparisons were made between EEN and supplementary PN groups for baseline and pre-operative body mass index (BMI) and weight loss, length of stay (LOS), stoma formation and post-operative complications. Analysis used chi-squared for categorical data and t-test for continuous data. Statistical significance was set at p < 0.05. Results: Forty-seven CD patients (29 males) with mean ± SD age (39.3 ± 14.9 years) received pre-operative nutritional optimisation. The EEN group ( n = 36) had higher baseline BMI (kg/m 2 ) (EEN: 23.6 ± 5.1 vs. PN: 18.0 ± 2.8, p < 0.001) and less unintentional weight loss at baseline (EEN: 4% ± 7 vs. PN: 14% ± 8, p < 0.001) compared with the supplementary PN group ( n = 11). There was no change between baseline and pre-operative BMI in the EEN group (baseline: 23.6 ± 5.1 vs. pre-operative: 23.9 ± 4.7, p = 0.151) but BMI increased in the PN group (baseline: 18 ± 2.8 vs. pre-operative: 19.8 ± 2.7, p = 0.038). Patients on EEN had shorter LOS (days) (EEN: 9 ± 8 vs. PN: 26 ± 19, p = 0.002) and a lower stoma formation rate (EEN: 22% vs. PN: 64%, p = 0.01) compared with patients on supplementary PN. Fewer patients had a high output stoma ( >1 l/day) in the EEN group compared with the supplementary PN group (EEN 38% vs. PN: 63%, p = 0.004). There were no significant differences between groups for other post-operative complications (ileus, wound breakdown, infection, reoperation and readmission). Conclusions: This service evaluation highlights the importance of pre-operative nutritional optimisation in CD patients. It shows that patients who can meet their nutritional requirements from EEN have better nutritional and surgical outcomes compared with patients who need supplementary PN.